The city of modern techniques - Menéndez, Eleonora (Universidad de Lima. Carrera de Arquitectura, 2020)
For decades, the so-called modern architecture and urbanism tried to modify the environment by applying new techniques. Le Corbusier was one of its remarkable supporters, and his poetical associations related to the full confidence in the technical era can be found in most part of his work performed during the first decades of the 20th century. This paper analyzes the technological innovations presented in an urban project of the first postwar period by Le Corbusier, Plan Voisin pour Paris, for considering it to be representative of the relation between technique and cultural transformations in the ways of the metropolitan social life.